Research into student learning And university teaching: Contrasting perspectives and levels of focus - Entwistle, Noel; Karagiannopoulou, Evangelia; Ólafsdóttir, Anna (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2018)
This article looks at research into student learning and university teaching, looking specifically at the differing perspectives and levels of focus typically adopted. The perspectives are those of researchers, students, and teachers, while the differing levels of focus are based on the individual students’ experiences of learning, the classroom contextand teaching-learning environment, and the institutional level and academics’ perceptions of teaching. These differences of perspective and focus are illustrated through three specific ,studies carried out by the authors, and suggest the need to capitalize on the differing perspectives to broaden the understanding of the multifarious influences on student learning